Is it possible with two words to touch three subjects? - Kašuba, Romualdas; Rudalevičienė, Regina (Lietuvos matematikos rinkinys, 2015)
In the paper an attempt to describe what a unexpected consequencies a comparison of some two (even strickingly similiar) matters might imply.